Engaged Scholarship in Gerontology: Frank Caro's Lifetime Contributions. Issue 2 (4th March 2022) - Sánchez, Mariano; Pinazo-Hernandis, Sacramento; Nadash, Pamela; Fitzgerald, Kelly; Stoeckel, Kimberly S.
ABSTRACT: Dr. Francis G. Caro, retired Professor of Gerontology at the University of Massachusetts Boston, Co-editor (1996–2005) and Editor-in-Chief (2005–2016) of the Journal of Aging and Social Policy, passed away on October 2, 2020. Caro dedicated most of his nearly 60 years of academic and professional activity to gerontology and services for older adults. This article offers a review of his contributions in four central areas of gerontology: the strengthening of long-term services and supports through integration of home care services with other domains, the expansion of how productive aging was socially understood and economically valued, the importance of rigorous program evaluation and ongoing methodological innovation, and the significance of age-friendly cities and communities, both in the United States and internationally. This review of Caro's work highlights his integral role in helping to place several topics on the gerontological agenda that are still relevant today, establishing him as an important contributor to the field. He also exemplified productive aging and how scholarship can be theoretically rigorous but also applied in meaningful ways to make a difference in individual lives and within communities.